Giant cell arteritis: Diagnostic accuracy of mr imaging of superficial cranial arteries in initial diagnosis-results from a multicenter trial - Klink, Thorsten; Geiger, Julia; Both, Marcus; Ness, Thomas; Heinzelmann, Sonja; Reinhard, Matthias; Holl-Ulrich, Konstanze; Duwendag, Dirk; Vaith, Peter; Bley, Thorsten Alexander (Radiology, 2014)
Purpose: To assess the diagnostic accuracy of contrast material-enhanced magnetic resonance (MR) imaging of superficial cranial arteries in the initial diagnosis of giant cell arteritis (GCA).
CRIS-Team Scopus Importer:2024-12-04